2014
DOI: 10.3390/e16126464
|View full text |Cite
|
Sign up to set email alerts
|

A Memristive Diode Bridge-Based Canonical Chua’s Circuit

Abstract: Abstract:A novel memristor circuit is presented, which is generated from the canonical Chua's circuit by replacing the Chua's diode with a first order memristive diode bridge. The circuit dynamical characteristics with the variations of circuit parameters are investigated both theoretically and numerically. It can be found that the circuit has three determined equilibrium points, including a zero saddle point and two nonzero saddle-foci with index 2. Specially, the circuit is non-dissipative in the neighborhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Chen et al were the first who replaced the nonlinear element in a nonlinear circuit with first-order memristive diode bridge. [29] Complex nonlinear phenomena including coexisting bifurcation modes and attractors have been discovered in this circuit. Another interesting memristive chaotic circuit was derived from the classical Chua's circuit by substituting the Chua's diode with the aforementioned generalized memristor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al were the first who replaced the nonlinear element in a nonlinear circuit with first-order memristive diode bridge. [29] Complex nonlinear phenomena including coexisting bifurcation modes and attractors have been discovered in this circuit. Another interesting memristive chaotic circuit was derived from the classical Chua's circuit by substituting the Chua's diode with the aforementioned generalized memristor.…”
Section: Introductionmentioning
confidence: 99%
“…[33] In this paper, we propose the simplest memristor-based circuit containing the first-order memristor bridge of Ref. [28], in regard to the aforementioned works [29][30][31][32][33]. The circuit has been designed in such a way that the firstorder memristive diode bridge acts as a nonlinear element.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many papers about the memristor [ 5 , 6 , 7 , 8 , 9 ]. In [ 6 ], a novel complex Lorenz system with a flux-controlled memristor is introduced and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, memristor-based chaotic circuits, most of all memristive Chua's chaotic circuits, have broadly been studied [3][4][5][6][7][8][9][10]. By substituting the nonlinear resistance elements, Chua's diodes, in various kinds of Chua's chaotic circuits, including classical Chua's circuit [3][4][5][6][7][8], canonical Chua's circuit [9][10][11], and modified Chua's circuit [12,13], with memristors of different nonlinearities [4,7,12], a wide class of memristive Chua's chaotic circuits are presented and some novel features of initial state dependent dynamical behaviors are reported [3,5,10,11]. However, no research literature related to memristor-based Colpitts chaotic oscillator can be found so far.…”
Section: Introductionmentioning
confidence: 99%